Self-report measure of dispositional flow experience in the video game context: Conceptualisation and scale development. Issue 159 (March 2022) - Cai, Xiaowei; Cebollada, Javier; Cortiñas, Mónica
Highlights: A 28-items flow scale, video game dispositional flow scale (VGDFS), is developed in this research. VGDFS faithfully conceptualises the dimensions of the original flow theory in the video game context. VGDFS is free to use flow scale without copyrights. The hierarchical antecedent model is the best structure to represent flow experience. Abstract: The flow theory has been widely applied to explain video game players' gaming and purchasing behaviour. However, due to the conceptual and empirical flaws of the current measurement instruments, researchers can hardly apply them to measure dispositional flow experience of adult video game players. In this research, we conceptualised flow experience and developed its measurement instrument in the video game context. To achieve these objectives, we conducted five phases with different participants in each of them: conceptualisation of the constructs and item generation ( n = 13), expert judging ( n = 5), pre-test ( n = 96), initial development and validation ( n = 289), and advanced development and validation ( n = 593). We applied both qualitative and quantitative analysis to conceptualise and measure flow experience of video game players, including grounded theory and several statistical tools of latent variable modelling. We obtained a scale of 28-items that performs well in the first-order model. Moreover, we tested three hierarchical structure of flow experience: unidimensional model, independent antecedent model, and hierarchical antecedent model. Results show that hierarchical antecedent model is the best structure to represent flow experience. We named our scale Video Game Dispositional Flow Scale (VGDFS).